PENGARUH CASH RATIO, NET PROFIT MARGIN (NPM), DAN FIRM SIZE (FS) TERHADAP DIVIDEND PAYOUT RATIO (DPR) PADA PERUSAHAAN SEKTOR INFRASTRUCTURE, UTILITIES, AND TRANSPORTATION - Amelia Maura; Agnes Reslita; Arie Dika Pratama; Yolanda Pebrina Cristy br Sitepu (Lembaga Penelitian dan Pengabdian Kepada Masyarakat-Universitas Darma Agung. (LPPM_UDA), 2022)
This study aimed at testing and analyzing the effect of Cash Ratio (CR), Net Profit Margin (NPM), and Firm Size (FS) on the Dividend Payout Ratio (DPR) in the Infrastructure, Utilities, And Transportation sector companies listed in Indonesia Stock Exchange in the 2014-2018 period. The research method applied in this study was quantitative research approach, the type of research was descriptive statistics, and the nature of the research was explanatory research. The population of this study was sixty six (66) companies in the Infrastructure, Utilities, And Transportation sector. By using sampling technique of purposive sampling technique, ten (10) companies in the Infrastructure sector, Utilities, And Transportation that met the criteria were taken as samples. The method of data analysis in this study was multiple linear regression analysis with classical assumption. The results of this study indicated that simultaneously Cash Ratio (CR), Net Profit Margin (NPM), and Firm Size (FS) had no effect and were insignificant on the Dividend Payout Ratio (DPR) in the Infrastructure, Utilities, And Transportation sector companies listed in Indonesia Stock Exchange in the 2014-2018 period with the results of Fcount ≤ Ftable or 2.719 ≤ 2.81 and significance of 0.055 ≥ 0.05. Partially Cash Ratio (CR) and Firm Size (FS) had effect on and significantly affected the Dividend Payout Ratio (DPR), while the Net Profit Margin (NPM) had no effect and significantly affected the Dividend Payout Ratio (DPR). The results of the analysis of the coefficient of determination obtained adjusted R2 value which showed the variation of the Dividend Payout Ratio (DPR) variable which could be explained by variations in the Cash Ratio (CR), Net Profit Margin (NPM), and Firm Size (FS) of 9.5% while as much as 90.5% was explained by variations in other variables.